Fatigue related EMG power spectrum changes during dynamic contractions in female rowers - Uzun, Selda (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2002., 2002)
The Surface Electrompography (SEMG) signal allows a good assessment of meuromuscular activity a noninvasive tool. While muscle fatigef is a complex multifaceted phenomenon, in sedentary subjects it is characterized by changes of spectral parameters. If these criteria are also valid for athletes, monitoring training and performance development as well as scientific research on muscular adaptations during intense physical exercise will be facilitated. For this purpose ten healthy female rowers of the Turkish National Team were selected. SEMG recordings were obtained from the muscles Vastus Lateralis (VL). The fatigue test with 80% Maximum Voluntary Contraction (MVC) consisted of two identical tests. First, the subjects performed repetitive auxotonic knee extensions to maintain for as long as possible (till exhaustion.) After a five-minute rest, the exercise protocol was rereated. The power spectrum was derived from the raw SEMG signal using the Fast Fourier Transform (FFT) algorithm. For the active phasa of each contraction cycle the Median Frequency (MDF) and the Mean Frequency (MNF) were computed from the EMG signal. In addition, the Borg's Category-Ratio Scaleğ (CR-10) was used to measure the perceived muscle exertion.The results of this study show that the inter-individual fatigue profiles differ in power spectrum. Differences are also noted for the first and the second experiments in terms of spectral values. But the MDF and MNF graphics both experiments are greatly similar. What is common for all the subjects is that there are periodic decreases and increases in their MDF and MNF values. Recruitment of larger motor units with higher discharge rates or cyclic recruitment of motor units during sustained auxotonic contractions may be the cause for these interesting findings. This result may represent a special muscular adaptation of elite rowers to intense muscular training.
Keywords: Electromyography.; Spectrum analysis.; Fatigue.